Biomechanical Properties and Correlation With Collagen Solubility Profile in the Posterior Sclera of Canine Eyes With an ADAMTS10 Mutation - Palko, Joel R. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. We examined the biomechanical properties and correlation with the collagen solubility profile of the posterior sclera in a canine model of primary open-angle glaucoma caused by the G661R missense mutation in the ADAMTS10 gene. METHODS. Scleral strips from ADAMTS10-mutant (affected) dogs and age-matched controls were collected. Viscoelastic properties (i.e., complex modulus and tan[δ]) were measured using dynamic mechanical analysis (DMA) with a 0.15% sinusoidal strain at different frequencies superimposed upon different preloads. A tensile ramp was performed following DMA. The collagen solubility profile was examined using a colorimetric hydroxyproline assay to determine the amount of soluble and insoluble collagen. The viscoelastic properties were compared between groups using linear mixed models for repeated measures at different preloads and frequencies. The correlation between the biomechanical properties and collagen content were evaluated using Pearson correlations. RESULTS. Complex modulus and tan(δ) were significantly lower in the affected group (P < 0.001), and the differences were consistent at different preloads and frequencies. The B value from the tensile ramp test also was significantly lower in the affected group (P = 0.02). The insoluble collagen was significantly lower in the affected group (P < 0.05) and correlated positively with the complex modulus (R = 0.88, P < 0.005). CONCLUSIONS. An inherently weaker and biochemically distinct posterior sclera was observed in dogs with the G661R missense mutation in ADAMTS10 before clinical indications of optic nerve damage. It remains to be shown whether and how the altered scleral biomechanics may affect the rate of glaucoma progression following intraocular pressure elevation.